Advances in the Diagnosis, Monitoring, and Progression of Oral Cancer through Saliva: An Update. (25th October 2022) - Rodríguez-Molinero, Jesús; del Carmen Migueláñez-Medrán, Blanca; Delgado-Somolinos, Esther; Carreras-Presas, Carmen Martín; López-Sánchez, Antonio Francisco
Abstract : The early detection of cancer, and in particular oral cancer, has been a priority objective of study in recent years. Saliva has been proposed as an easy-to-obtain means of providing the necessary information to diagnose malignant lesions in the oral cavity, since it can be obtained very easily and completely noninvasively. There are a number of molecules, known as biomarkers, which may be involved in the malignant transformation of oral lesions, and which have different natures. The involvement of proteins ("proteomics"), metabolites ("metabolomics"), and even certain genes in the structural changes of altered tissue has been investigated in order to establish validated parameters for the early diagnosis of oral cancer. In addition, the development of new analytical assay methods that can reduce costs and obtain better results in terms of sensitivity and specificity has been a key point in recent research in this field. Even though there are numerous biomarkers with results showing high sensitivity and specificity, there is still a need for more studies, with a larger sample and with analytical methods that can constitute a real advance in time and cost. Although salivary biomarkers are a promising new diagnostic tool for oral cancer, for the moment they do not replace biopsy as the "gold standard".